2019
DOI: 10.48550/arxiv.1912.09962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calorimeters for the FCC-hh

M. Aleksa,
P. Allport,
R. Bosley
et al.

Abstract: The future proton-proton collider (FCC-hh) will deliver collisions at a center of mass energy up to √ s = 100 TeV at an unprecedented instantaneous luminosity of L = 3 10 35 cm −2 s −1 , resulting in extremely challenging radiation and luminosity conditions. By delivering an integrated luminosity of few tens of ab −1 , the FCC-hh will provide an unrivalled discovery potential for new physics. Requiring high sensitivity for resonant searches at masses up to tens of TeV imposes strong constraints on the design o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Highly granular noble-liquid sampling calorimetry was proposed for a possible FCC-hh experiment [7,231,232]. It has been shown that, on top of its intrinsic excellent electromagnetic energy resolution, noble-liquid calorimetry can be optimized in terms of granularity to allow for 4D imaging, machine learning or, in combination with the tracker measurements, particle-flow reconstruction.…”
Section: Calorimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Highly granular noble-liquid sampling calorimetry was proposed for a possible FCC-hh experiment [7,231,232]. It has been shown that, on top of its intrinsic excellent electromagnetic energy resolution, noble-liquid calorimetry can be optimized in terms of granularity to allow for 4D imaging, machine learning or, in combination with the tracker measurements, particle-flow reconstruction.…”
Section: Calorimetrymentioning
confidence: 99%
“…Currently, a granularity of ∆θ × ∆ϕ = 2.5 mrad × 8.2 mrad (5.4 mm × 17.7 mm) is foreseen in the first calorimeter compartment to optimize the π 0 rejection. Single-particle simulations of electrons and photons have resulted in a stochastic term of 8.2 % [231,232] for the standalone electromagnetic energy resolution. Exploiting the full 4D imaging information, it was demonstrated that a deep-neural-network analysis can achieve a single-π − resolution stochastic term of 37 % (B = 4 T) for such a highly granular noble-liquid calorimeter complemented with a scintillator-iron HCAL.…”
Section: Calorimetrymentioning
confidence: 99%
“…Machine-learning algorithms can offer this flexibility as they are typically differentiable by construction, and can also easily adapt to changing conditions. However, neither those algorithms that rely on a regular geometry (such as convolutional neural network based approaches [161][162][163][164][165]), nor algorithms based on dense neural networks alone that make no assumptions at all on the structure of the problem, are applicable: the former cannot generalize to irregular geometries, and the latter cannot fit resource constraints. In addition, recurrent algorithms cannot be made really generic, as conceptually they rely on a certain ordering of the inputs.…”
Section: Modeling Of Pattern Recognition and Event Reconstruction Pro...mentioning
confidence: 99%
“…A prototype of a baseline FCC-hh detector that could fulfill the above requirements has been designed by the FCC-hh collaboration [70][71][72]. The detector has a diameter of 20 m and a length of 50 m, with dimensions comparable to the ATLAS detector.…”
Section: Detector Requirementsmentioning
confidence: 99%